Study of Effect of Lignocaine in Prevention of Pain and Withdrawal Movements after Intravenous Rocuronium Injection - Prasai, Adim; Prasai, Abha (Nepal Medical College Journal, 2021)
Rocuronium bromide is an amino-steroidal neuromuscular blocking drug frequently used in anesthetic practice. It causes intense discomfort and pain at the site of injection and was reported by 50-80% of patients. Use of local anesthetic agents have been widely supported for prevention of pain. We studied the effect of lignocaine in prevention of pain during rocuronium injection in 160 patients. Preservative free lignocaine at a dose of 1mg/kg was given intravenously after applying tourniquet. Venous occlusion was released after one minute and 0.6mg/kg of rocuronium was injected. Pain score was recorded according to a 5-point likert scale of pain and withdrawal was graded with 4-point scale. Total number of female patients was 96 (60%) and male patients was 64 (40%). Among them, 131 (81.9%) fell in ASA I and remaining 29 (18.9%) in ASA II. One hundred and thirty-eight (86.3%) patients did not complain of pain when asked. Mild and moderate pain was seen in 17 (10.6%) and 4 (2.5%) patients respectively whereas 1 (0.6%) patient had severe pain. Wrist movement was noted in 10 (6.25%) patients and remaining 150 (93.75%) had no withdrawal movement during the injection of rocuronium. Pre-treatment with intravenous lignocaine helps in prevention of pain and withdrawal movements caused by intravenous rocuronium injection in patients.